Membangun Narasi Visual Melalui Desain Karakter: Studi Kasus Karakter Ikonik - Alex Sapmayada (Penerbit dan Percetakan, CV. Picmotiv, 2024)
This study discusses the important role of character design in building effective visual narratives through a case study of iconic characters in pop culture. Character design serves as a narrative medium that is able to convey stories and build emotional connections with the audiences. This study uses a qualitative method with a case study approach, where data is collected through content analysis on online discussion platforms such as Fandom and YouTube, as well as an open-ended questionnaire survey. The results of the study indicate that visual elements such as silhouette, palette, and exaggeration in character design can provide story clues and support the storyline consistently. The findings are in line with the theory of visual storytelling which states that each visual element provides certain values and messages. This study is expected to provide insights for designers to create characters that are not only memorable but also able to become strong and relevant narrative media.